An L-shaped association between lymphocyte-to-monocyte ratio and erectile dysfunction in NHANES 2001–2004 - Donggang Shan; Chenze Yan; Zhong Jia (Scientific Reports)
Abstract This study aimed to explore the relationship between the lymphocyte/monocyte ratio (LMR) and erectile dysfunction (ED) in adult men in the United States using a comprehensive dataset. A cross-sectional study design was used to analyze the relationship between the lymphocyte-to-monocyte ratio (LMR) and the prevalence of erectile dysfunction (ED) among adult male participants in the NHANES 2001–2004 dataset. Statistical analyses were performed to adjust for potential confounders and explore non-linear associations, with LMR categorized into quartiles to investigate the relationship with ED prevalence. There was an L-shaped relationship between LMR and ED. The odds of ED decreased as LMR levels increased, but beyond a value of 3.50, the protective effect plateaued. Specifically, the odds of ED significantly decreased for LMR values ≤ 3.50 (OR = 0.67, 95% CI: 0.49–0.90, p = 0.009). Beyond an LMR of 3.50, there was no significant further reduction in the odds of ED, indicating a diminishing protective effect past this threshold. There is a distinctly L-shaped and negative correlation between LMR and ED in the NHANES dataset from 2001 to 2004.